CALCRETES FROM A LATE QUATERNARY INTERFLUVE IN THE GANGA PLAINS, INDIA: CARBONATE TYPES AND ISOTOPIC SYSTEMS IN A MONSOONAL SETTING - Sinha R.; Tandon S.K.; Ghazanfari P.; Sanyal P.; Gibling M.R.; Stuben D.; Berner Z. (My University, 2006)
Calcretes are abundant in Late Quaternary channel and floodplain strata of the southern Ganga plains. In a key section at Kalpi, pedogenic carbonates (nodules, rhizoconcretions, and powdery carbonate) are present within aggradational floodplain deposits, where they correspond to relatively high monsoonal precipitation and river discharge. In contrast, groundwater carbonate has cemented degradational surfaces (discontinuities), which correspond with periods of relatively low precipitation. Mixed groundwater and pedogenic calcretes are present in the deposits of small interfluve channels, and reworked nodules line degradational surfaces and locally fill channels. Most carbonates show alpha fabrics that include floating textures, shrinkage crack fills, and grain coatings. The predominance of alpha fabrics is unexpected, but is characteristic of calcretes across dryland and seasonal parts of northern India, where soil formation led to only weakly developed or poorly preserved beta fabrics. Interpretation of δ13C and δ18O values of bulk and microdrilled calcrete samples suggests relatively little variation in precipitation and vegetation types through the sampled interval at Kalpi. Floodplain deposits were vegetated with a mixture of C4 and C3 plants (predominantly C4), with a higher proportion of C3 plants associated with channel deposits. This apparent lack of variation is surprising because the sampled interval represents at least 60,000 years of Marine Isotope Stages 3-5, during which climate models suggest that Asia experienced radical fluctuations in monsoon intensity and precipitation. Some of the apparent lack of variation may be explained by preferential preservation of aggradational strata that represent relatively active monsoonal periods, as well as by the mixing of drier floodplain (C4) and riparian (C3) vegetation. However, local departures from the regionally based climate model cannot be ruled out. A modest upsection increase in C4 plants may represent increased aridity and lower atmospheric CO2. Isotopic analysis of organic matter from floodplain pedogenic nodules suggests a higher C3 plant contribution than carbonate-based data would suggest. The preserved organic matter may reflect the annual average biomass in the soil, whereas carbonate formation may have taken place mainly during the drier season when respiration of C4 plants was more important. In interfluve settings such as Kalpi, seasonality may strongly affect the C3-C4 system, with preferential preservation of only part of the biomass. © 2006 Elsevier B.V. All rights reserved.
Keywords: C; CALCRETE; CARBON AND OXYGEN ISOTOPES; DISCONTINUITY; INDIA; INTERFLUVE; MONSOON PRECIPITATION; PEDOGENIC AND GROUNDWATER CARBONATE; QUATERNARY; VEGETATION; Cenozoic::Quaternary; Кайнозой::Четвертичная